Course, Pathophysiology, Bacteriological Examination And Treatment Of Salmonellosis In Rabbits And Poultry - I.Yu.Sultanova; S.M. Urazaliev (Universitas Muhammadiyah Sidoarjo, 2022)
The article considers the concept of brand management of trade enterprises, as well as its essence in relation to modern conditions of transformation of market relations. The specific functions of the brand management of trade enterprises in terms of marketing orientation in the context of its elements are identified.